Mensuração de custos e resultados por projetos: estudo comparativo de métodos de custeio em empresa produtora de bens de capital sob encomenda - Luz, Mauricio Santos da (Universidade do Vale do Rio do Sinos, 2007)
This study aims to analyze the model of cost measuring, results and effects on the management model through the direct-costing method compared to the current costing method used in the studied company that is the absorption-costing method. In order to reach the target, one hundred and eight projects, carried out in the company, were analyzed. The results from each project were classified in four classes of projects, according to each equipment features. The comparisons of cost measuring were shown through income statements by class of project between the two costing methods, and by analyzing the results, it was possible to check mainly their effects on the company management. Thus, the study is classified as an applicable and quantitative research considering the data of the projects. The hypothetical-deductive method was used, because of the tested conjectures, or rather saying, the costing methods. Statistical analyses were also used in the comparisons, such as the regression analysis to help with the incom
Keywords: custeio direto; custeio por absorção; mensuração de custos; métodos de custeio; modelo de gestão; absorption-costing method; cost measuring; direct-costing method; management model; Ciências Sociais Aplicadas